If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15(x + -5) = 105 Reorder the terms: 15(-5 + x) = 105 (-5 * 15 + x * 15) = 105 (-75 + 15x) = 105 Solving -75 + 15x = 105 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '75' to each side of the equation. -75 + 75 + 15x = 105 + 75 Combine like terms: -75 + 75 = 0 0 + 15x = 105 + 75 15x = 105 + 75 Combine like terms: 105 + 75 = 180 15x = 180 Divide each side by '15'. x = 12 Simplifying x = 12
| 2a-(-18)=18 | | 4(x-15)=168 | | 2x+10+3x+10=90 | | 49x^3-xy^2= | | (x-4)2+(y+5)2=25 | | X-2/5=-4 | | 81-4y^2= | | 6x-11=-5x+6.6 | | 8h-19=15 | | 6x+13+4x-3=180 | | -7.3x=-12.4-1.1x | | 4(4x+3)+7(x-3)= | | 6s+40=184 | | 3(2x-5)/2=8 | | 4y=72^1/5 | | -10+n=-2n+5 | | 3(2x-5)/28 | | 7d=6d-7 | | -10-7-9f=-6f+10 | | 2.70xX=6.96 | | 23u+9=78 | | -10-6w=6-4w | | 3x^2+5x-1=4 | | 7s+35=112 | | -3c-1=-9-2c | | 27j-54= | | 1-1/6 | | 25=x-1/6x | | 7h=6h+6 | | 5x+2+3x+6= | | -m+1=-2m+10 | | 51-w=34.5 |